2014
DOI: 10.1177/0017896914558643
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco cessation through community pharmacies: Knowledge, attitudes, practices and perceived barriers among pharmacists in Penang

Abstract: Objectives: Tobacco cessation is the primary goal of tobacco control measures. Community pharmacists are possible providers of tobacco cessation counselling due to their close contact with the public and the availability of non-prescription nicotine replacement therapies in pharmacies. However, community pharmacists often do not provide tobacco cessation interventions. This study aimed to assess the knowledge, attitudes, practices and perceived barriers to tobacco cessation counselling among community pharmaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…This study also identified the lack of materials for smoking services as a barrier to service provision, a result consistent with a related study conducted in Thailand by Thananithisak et al [ 10 ], and other studies [ 26 , 28 ]. This is despite that materials to aid smoking cessation could be requested without any charge from the Action on Smoking and Health Foundation Thailand (ASH Thailand).…”
Section: Discussionsupporting
confidence: 91%
“…This study also identified the lack of materials for smoking services as a barrier to service provision, a result consistent with a related study conducted in Thailand by Thananithisak et al [ 10 ], and other studies [ 26 , 28 ]. This is despite that materials to aid smoking cessation could be requested without any charge from the Action on Smoking and Health Foundation Thailand (ASH Thailand).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, although the majority of respondents supported the role of CPs in providing WMS, only a small percentage reported utilizing these services (Verma et al, 2018). A lack of patient demand was also perceived to be a barrier for other pharmacy-related services in Malaysia, such as tobacco cessation service (Taha and Guat Tee, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of smoking cessation services, the lack of commitment amongst smokers to quit echoed the findings of a previous study conducted in Penang, Malaysia. [38] A recent national survey noted only 1 in 10 of the smokers in Malaysia with the intention to quit actually translated their intention into action by contacting a healthcare provider. [39] Unearthing the reasons behind this reluctance to seek help is likely to provide valuable insights.…”
Section: Discussionmentioning
confidence: 99%